Morphometric characterization of local geese in the Valley of Kashmir - HAMADANI, HENNA; KHAN, A A; MIR, M S; BANDAY, M T; GANAI, T A S; HAMADANI, A (The Indian Journal of Animal Sciences, 2014)
An extensive study was carried out in the geese rearing areas of Kashmir Valley to record the morphometric parameters which included external body measurements and visceral measurements of local geese. Among the external body measurements, body weight, bill dimensions, knob diameter, neck dimensions, length from tip of bill to tail tip and wing span was significantly more in males than females. Among the visceral measurements, only jejunum length showed a significant difference between the sexes. In females, the mean oviduct length was 38.5±8.5 cm and the mean weight of ovaries was 12.51±2.225 g. In males, left testicle was found significantly larger than the right one in terms of length and breadth but the weight of left and right testicle did not vary significantly.